A simultaneous model of the Swedish Krona, the US Dollar and the Euro - Hans Lindblad; Peter Sellin (Sveriges Riksbank, 2006)
In this paper we simultaneously estimate the real exchange rates between the Swedish Krona, the US Dollar and the Euro. A prime candidate for explaining the exchange rate movements is relative potential output. Since this variable is unobservable, cyclical and potential output are estimated in an unobserved components framework together with a Phillips curve. Our empirical exchange rate results are in line with theory. Increases in relative potential output and the terms of trade strengthen the exchange rate, while a relative increase of the fraction of middle-aged people in the population and budget deficits depreciate the exchange rate. The estimates suggest that the recent deterioration of the relative budget situation for the US versus Europe is a prime candidate for explaining the USD/EUR exchange rate change lately.
Keywords: C32; E31; F31; F41; 330; equilibrium real exchange rate; expectations augmented Phillips curve; unobserved-components model; Kleines-Land-Modell; Wechselkurstheorie; Wirtschaftspotenzial; Kaufkraftparität; Phillips-Kurve; Schweden